ANALISIS KEBUTUHAN GABI (GAME ANDROID BAHASA INDONESIA) SEBAGAI MEDIA PEMBELAJARAN MKU BAHASA INDONESIA - Hanindya Restu Aulia; Afrinar Pramitasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
MKU Bahasa Indonesia has been less desirable so it needs an update in the form of android game containing the content of the Indonesian Constitutional Court. GABI requirement analysis was obtained based on questionnaire and FGD result, FGD was conducted with Lecturer of PBSI which was able to MKU Bahasa Indonesia in Unikal. Meanwhile, the questionnaire was distributed to students of Faculty of Economics, Faculty of Health Sciences, and Faculty of Teacher Training and Education. The results of this research needs analysis 1) MKU learning during this less desirable by the students so that the required learning media is aktraktif, 2) MKU no university developing game loaded material MKU Bahasa Indonesia, 3) GABI development based on MKUmanual of Dikti.Keywords: android, Indonesian, games.